Implications of the Estrogen Receptor Coactivators SRC1 and SRC2 in the Biological Basis of Gender Incongruence - Karla del Valle Ramírez, Pre-doc; Rosa Fernández, PhD; Enrique Delgado-Zayas, Pre-doc; Esther Gómez-Gil, MD; Isabel Esteva, MD; Antonio Guillamon, MD; Eduardo Pásaro, PhD (Sexual Medicine, 2021)
ABSTRACT: Introduction: Brain sexual differentiation results from the effects of sex steroids on the developing brain. The presumptive route for brain masculinization is the direct induction of gene expression via activation of the estrogen receptors α and β and the androgen receptor through their binding to ligands and to coactivators, regulating the transcription of multiple genes in a cascade effect. Aim: To analyze the implication of the estrogen receptor coactivators SRC-1, SRC-2, and SRC-3 in the genetic basis of gender incongruence. Main Outcome Measures: Analysis of 157 polymorphisms located at the estrogen receptor coactivators SRC-1, SRC-2, and SRC-3, in 94 transgender versus 94 cisgender individuals. Method: Using SNPStats software, the allele and genotype frequencies were analyzed by χ2, the strength of the association was measured by binary logistic regression, estimating the odds ratio for each genotype. Measurements of linkage disequilibrium and haplotype frequencies were also performed. Results: We found significant differences at level P < .05 in 8 polymorphisms that correspond to 5.09% of the total. Three were located in SRC-1 and 5 in SRC-2. The odds ratio analysis showed significant differences at level P < .05 for multiple patterns of inheritance. The polymorphisms analyzed were in linkage disequilibrium. The SRC-1 haplotypes CGA and CGG (global haplotype association P < .009) and the SRC-2 haplotypes GGTAA and GGTAG (global haplotype association P < .005) were overrepresented in the transgender population. Conclusion: The coactivators SRC-1 and SRC-2 could be considered as candidates for increasing the list of potential genes for gender incongruence. Ramírez KDV, Fernández R, Delgado-Zayas E, et al. Implications of the Estrogen Receptor Coactivators SRC1 and SRC2 in the Biological Basis of Gender Incongruence. Sex Med 2021;9:100368.